ACJS 2020 Presidential Address: From Local to Global: Scaling Up and Expanding Out the Study of Unresolved Homicides. (29th July 2021) - Unnithan, N. Prabha
Abstract: A plea for scaling up (i.e., examining the global dimensions) and expanding out (i.e., considering indirect, alternative and complementary measures) of local crime and criminal justice phenomena is made in this paper. The implications and benefits of doing so are illustrated by utilizing the study of unresolved (or cold case) homicides, which are usually conceived as events responsive to localized co-victim, police, and prosecutorial actions. Cross-nationally, the homicide rate is found to be significantly correlated to the formal contact rate and conviction rate (i.e., as indicators of criminal justice system responsiveness to such cases). Inter-woven with the discussion is a personal narrative of how the author came to develop an interest in this and related topics.